3(3x-2)=7(x+6)+7

Simple and best practice solution for 3(3x-2)=7(x+6)+7 equation. Check how easy it is, and learn it for the future. Our solution is simple, and easy to understand, so don`t hesitate to use it as a solution of your homework.

If it's not what You are looking for type in the equation solver your own equation and let us solve it.

Solution for 3(3x-2)=7(x+6)+7 equation:


Simplifying
3(3x + -2) = 7(x + 6) + 7

Reorder the terms:
3(-2 + 3x) = 7(x + 6) + 7
(-2 * 3 + 3x * 3) = 7(x + 6) + 7
(-6 + 9x) = 7(x + 6) + 7

Reorder the terms:
-6 + 9x = 7(6 + x) + 7
-6 + 9x = (6 * 7 + x * 7) + 7
-6 + 9x = (42 + 7x) + 7

Reorder the terms:
-6 + 9x = 42 + 7 + 7x

Combine like terms: 42 + 7 = 49
-6 + 9x = 49 + 7x

Solving
-6 + 9x = 49 + 7x

Solving for variable 'x'.

Move all terms containing x to the left, all other terms to the right.

Add '-7x' to each side of the equation.
-6 + 9x + -7x = 49 + 7x + -7x

Combine like terms: 9x + -7x = 2x
-6 + 2x = 49 + 7x + -7x

Combine like terms: 7x + -7x = 0
-6 + 2x = 49 + 0
-6 + 2x = 49

Add '6' to each side of the equation.
-6 + 6 + 2x = 49 + 6

Combine like terms: -6 + 6 = 0
0 + 2x = 49 + 6
2x = 49 + 6

Combine like terms: 49 + 6 = 55
2x = 55

Divide each side by '2'.
x = 27.5

Simplifying
x = 27.5

See similar equations:

| 1/2x-5=3x-10 | | 9x+6y=150 | | 283=3.14(5)l+25 | | 2(5x-3)-1=13 | | 6v+6=4v+2(v+3) | | 3.1-0.2a=1.5 | | m+m+5+m+8=84 | | 5-2p=7 | | -7.26+18p=6p-2.22+12.3p | | 3x+4y=75 | | 4x-48=36 | | 25.50x=12.50 | | -1=c-6 | | 6x+(3x-2)=14 | | -7v-5=-5v-9 | | x^2-7/3x-2/3 | | X+-5=6 | | -20+2x=30 | | 184=6y+4 | | -2n(9-10n)= | | 25.50=13.50 | | 8/3=32/x | | 6.2h+51.4h=4.8h+5 | | 6x+10=-7x-3 | | -2=a+6 | | 12(1)-4y=16 | | -5(-a-8)=16-a | | -17.7r=-16r+18.02 | | 7x+3y=-24 | | 12(0)-4y=16 | | 9+13x=35+26x | | -1/2(6-10x)+4=1/4(12x-20) |

Equations solver categories